Trading N and O: asymmetric syntheses of beta-hydroxy-alpha-amino acids via alpha-hydroxy-beta-amino esters - Davies, S; Fletcher, A; Frost, AB; Lee, J; Roberts, P; Thomson, J (2013)
Both diastereoisomers of 2-amino-3-hydroxybutanoic acid and 2-amino-3-hydroxy-3-phenylpropanoic acid have been prepared from enantiopure α-hydroxy-β-amino esters via the intermediacy of the corresponding cis- and trans-aziridines. Aminohydroxylation of two α,β-unsaturated esters produced enantiopure 2,3-anti-α-hydroxy-β-amino esters in >99:1 dr. Subsequent epimerisation at the C(2)-position via a sequential oxidation/diastereoselective reduction protocol gave the corresponding enantiopure 2,3-syn-α-hydroxy-β-amino esters in >99:1 dr. These syn- and anti-substrates were then converted into the corresponding N-Boc protected cis- and trans-aziridines, respectively, via a three step reaction sequence: (i) hydrogenolysis and in situ N-Boc protection; (ii) OH-activation; and (iii) aziridine formation. Subsequent regioselective ring-opening of the C(3)-methyl-aziridines with Cl3CCO2H proceeded with inversion of configuration to give the corresponding 2-amino-3-trichloroacetate esters, whereas the analogous reaction with the C(3)-phenyl-aziridines resulted in rearrangement to the corresponding oxazolidin-2-ones with retention of configuration. In each case, hydrolysis of the products from these ring-opening reactions produced the corresponding enantiopure β-hydroxy-α-amino acids as single diastereoisomers. © 2013 Elsevier Ltd. All rights reserved.